Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.1097/prs.0b013e3181addc50
|View full text |Cite
|
Sign up to set email alerts
|

Isolated Capitate Shortening Osteotomy for the Early Stage of Kienböck Disease with Neutral Ulnar Variance

Abstract: This technique is a simple and reliable method with which to manage the early stages of Kienböck disease with neutral ulnar variance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
34
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 27 publications
4
34
0
1
Order By: Relevance
“…1 In their experience using radial recession osteotomy in Kienböck's disease, Quenzer et al found radiographic healing and improvement of the lunate density in some patients at least 12 months after surgery. 23 In their experience of height reconstruction and core revascularization of the lunate in early stage III of Kienböck's disease, Bochud and Buchler 24 found signs of revascularization in approximately half of their cases at 18 to 36 months after surgery.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…1 In their experience using radial recession osteotomy in Kienböck's disease, Quenzer et al found radiographic healing and improvement of the lunate density in some patients at least 12 months after surgery. 23 In their experience of height reconstruction and core revascularization of the lunate in early stage III of Kienböck's disease, Bochud and Buchler 24 found signs of revascularization in approximately half of their cases at 18 to 36 months after surgery.…”
Section: Discussionmentioning
confidence: 97%
“…9 Capitate shortening osteotomy, described first by Almquist, 10,11 is a technique that has been advocated in Kienböck's disease with ulnar neutral or positive variance and Lichtman stage I to IIIA. 1,12,13 Capitate shortening decreases load transfer across the radiolunate joint. 14, 15 Almquist reported 83% revascularization and healing of the fragmented lunate after capitate shortening with capitohamate fusion.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…For early disease, patients are instructed on the literature regarding natural history and may choose from observation vs. revascularization (direct or indirect) on an individual basis [1,2,6,30]. With progressive collapse, most patients choose direct revascularization with a pedicled bone flap over indirect revascularization by core decompression/osteotomy [10,13,22]. For an unsalvageable lunate, patients are instructed that the standard surgical options are proximal row carpectomy (PRC), scaphotrapeziotrapezoid (STT) fusion, scaphocapitate (SC) fusion, or total wrist fusion (TWF) [5,7,8,16,18,26,32].…”
Section: Introductionmentioning
confidence: 99%
“…1-8 Treatment options range from conservative measurements to surgical interventions. 9-12 Several authors advocated a biomechanical approach to reduce load transmission on the necrotic lunate, [13][14][15][16][17][18][19] and good clinical results have been reported in joint leveling procedures such as radial shortening or ulnar lengthening 20-22 and in radial or ulnar wedge osteotomy. 23,24 Hori et al 25 introduced a biological approach of revascularization for necrotic bones based on their experimental results.…”
mentioning
confidence: 99%